(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:The observation of ketonuria and its severity in post- term pregnancies can be considered as one of the most important biochemical markers, which can help the obstetrician to predict the adverse outcome of post-term pregnancy with some sort of precision. Objective:To assess the effect of maternal ketonuria on fetal wellbeing in pregnant woman with post-term pregnancy, estimate the frequency of amniotic fluid volume changes in different degrees of ketonuria and to estimate the frequency of non-stress test abnormalities according to the severity of ketonuria. Methods: Two hundred and fifty post-term pregnant women divided into pregnant woman with ketonuria of different severity (27) and pregnant woman without ketonuria (223). Ketone bodies were tested in urine. Fetal testing had been done for all of them in terms of non stress test and amniotic fluid volume assessment in term of amnioticfluid index. Results: Ketonuria was found in 10.8% of post-term pregnant woman and 62.9% of them had moderate to severe ketonuria. Oligohydramnios had been observed in 62.9% and 22.4% of pregnant woman with ketonuria and those without ketonuria, respectively. 4(80%) with severe ketonuria had oligohydramnios. Abnormal non-stress test was observed in 85.1% and 45.7% of those pregnant women with and those without ketonuria, respectively. There is a significant statisticalassociation between the presence of ketonuria and the result of fetal testing. Conclusion: Ketonuriawas significantly associated with oligohydramnios and abnormal results of non-stress test. Higher frequency of oligohydramnios and abnormal results of non-stress test among those with severe ketonuria. Keywords:Post-term, ketonuria, oligohydramnios, non-stress test